2016
DOI: 10.1103/physrevlett.116.227201
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transitions in Disordered Systems: The Example of the Random-Field Ising Model in Four Dimensions

Abstract: By performing a high-statistics simulation of the D ¼ 4 random-field Ising model at zero temperature for different shapes of the random-field distribution, we show that the model is ruled by a single universality class. We compute to a high accuracy the complete set of critical exponents for this class, including the correction-to-scaling exponent. Our results indicate that in four dimensions (i) dimensional reduction as predicted by the perturbative renormalization group does not hold and (ii) three independe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
79
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(85 citation statements)
references
References 56 publications
6
79
0
Order By: Relevance
“…Supersymmetry predicts η = η (moreover, the D-dimensional RFIM η = η are predicted to be equal to the anomalous dimension of the pure Ising model in dimension D − 2). Extensive numerical simulations at zero temperature showed that these relations fail at D = 3 [23] and D = 4 [25], but they are valid with good accuracy at D = 5 [26]. These numerical results suggest that supersymmetry may be really at play at D = 5.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…Supersymmetry predicts η = η (moreover, the D-dimensional RFIM η = η are predicted to be equal to the anomalous dimension of the pure Ising model in dimension D − 2). Extensive numerical simulations at zero temperature showed that these relations fail at D = 3 [23] and D = 4 [25], but they are valid with good accuracy at D = 5 [26]. These numerical results suggest that supersymmetry may be really at play at D = 5.…”
mentioning
confidence: 75%
“…The system has a ferromagnetic phase at small σ, that, upon increasing the disorder, becomes paramagnetic at the critical point σ c . Here, we work directly at σ c , namely at 6.02395 ≈ σ c (D = 5) [26] and at 4.17749 ≈ σ c (D = 4) [25]. We consider two correlation functions, namely the connected and disconnected propagators, C (con) xy and C (dis) xy :…”
mentioning
confidence: 99%
“…Unfortunately, in the present D = 3 case, we can not draw a definite conclusion on the validity of the two-exponent scaling scenario. Additional work is under way to tackle this problem at higher dimensions (D > 3) [80].…”
Section: Resultsmentioning
confidence: 99%
“…The most obvious generalization is of course the RFIM in higher dimensions (see, e.g., [80]). However, similar ideas can be applied to many disordered systems and should be useful when one needs to take derivatives, or to perform reweighting extrapolations, with respect to the disorder-distribution parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there are two types of RFM/RAM spin models. The first is the Ising model, where the spins are scalars S i = ±1 and are randomly pointing either parallel or antiparallel to each other in the ground state [55][56][57][58][59][60][61][62]. The second type is the Heisenberg model, where the spins are vectors S i that in the ground state are pointing noncollinearly in random directions [63][64][65][66][67][68].…”
Section: Introductionmentioning
confidence: 99%